Using Macro-invertebrates as Bio-indicator for Assessment Water Quality of Bodies in Ngoc Thanh Commune, Phuc Yen District, Vinh Phuc Province - Hieu, Nguyen Van; Lien, Bui Thuy; Vinh, Nguyen Van (VNU Journal of Science: Natural Sciences and Technology, 2016)
Abstract: This study aims to assess the environmental condition of selected water bodies in Ngọc Thanh commune, Phuc Yen district, Vinh Phuc province. Water quality was assessed by using macro-invertebrates as bio-indicators. Field collection from 20 sampling sites in December 2015 has yielded 71 aquatic macro-invertebrates families, 64 of which were included in the BMWP VIET scoring system. Among 20 sampling sites, eleven sites (from site S10 to site S20) were classified at the α-Mesosaprobe level (quite polluted), with ASPT scores ranging from 3.0 to 4.9; two sites (S7 and S8) with ASPT scores 5.5 and 5.7 respectively, were classified at the β-Mesosaprobe (quite polluted); seven sites (from site S1 to S6 and site S9) with ASPT scores ranging from 6.0 to 7.9, were classified at the Oligosaprobe level (fairly clean). Mostly of sampling sites in the study area with human activities (construction, tourism, agriculture…), negatively affected the water quality, with pollution level at these sites classified at α- and β-Mesosaprobe levels. Keywords: Macro-invertebrates, bio-indicator, BMWP, water quality, Ngoc Thanh commune.